Anti‐immigration policy in the destination country and skilled–unskilled wage inequality in a source economy with or without unemployment. (18th July 2019) - Chaudhuri, Sarbajit
Abstract: This paper is aimed at theoretically examining the consequence of the anti‐immigration policy adopted in the destination country on the skilled–unskilled wage inequality in a source nation using a couple of two‐sector, specific‐factor general equilibrium models in both the presence and absence of unemployment. Emigration requires incurring some capital cost for professional skill formation on the part of every prospective emigrant that adds to the opportunity cost of emigration. The authority of the destination country determines the number of visas to be granted and hence directly controls the magnitude of skilled emigration from the source country. In the migration equilibrium, the expected skilled wage income abroad is equal to the opportunity cost of emigration. In both the presence and absence of unemployment of unskilled labor, the outcome of the policy on the wage inequality crucially hinges on both the magnitude of the fixed cost of emigration and the technological factors. In the specific‐factor Harris–Todaro model, the degree of imperfection in the unskilled labor market is an additional factor. Finally, some policy recommendations have been made for protecting the interest of the poor unskilled workforce.